IXTISOSLASHTIRILGAN TA’LIM JARAYONIDA O‘QUVCHILARNING IQTIDORINI RIVOJLANTIRISHGA OID JAHON TAJRIBALARI TAHLILI - Pazilov, M.A. (SCIENCE and SOCIETY, 2023)
The article reflects on the analysis of world experiences on the development of students ' talents in the process of specialized education.
Keywords: Education; discovery; invention; Japan; turnstile; Europe; assembly; eurotalant; Paris; specialized education; gifted children